Repérages discursifs et traduction - Guillemin-Flescher, Jacqueline (Studia Romanica Posnaniensia, 2007)
In the article the- problem of differences between texts in French and English is discussed in relative clauses, indicative (deictic) expressions and dislocations. It appears that no grammatical restrictions determine the use of one or another form in both languages discussed here. These are restrictions which should be considered on another level, namely, on the level of various ways of placing points of reference in French as related to the sender of the communication, and in English as related to its receiver.